Early Jurassic adakitic rocks in the southern Lhasa sub-terrane, southern Tibet: petrogenesis and geodynamic implications - Shui, Xinfang; He, Zhenyu; Klemd, Reiner; Zhang, Zeming; Lu, Tianyu; Yan, Lili (Geological Magazine, 2018)
Cretaceous–Miocene adakitic rocks in the southern Lhasa sub-terrane have been intensively investigated, while possible Early Jurassic adakitic rocks in this area have been largely neglected. Petrological and geochemical studies revealed adakitic affinities of an Early Jurassic quartz diorite intrusion with mafic enclaves and three tonalite bodies from the Jiacha area in the southern Lhasa sub-terrane. Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) zircon U–Pb dating suggests crystallization ages of 199–179 Ma for these rocks. Both quartz diorites and tonalites have typical adakitic geochemical characteristics such as high Al2O3 (15.14–18.22 wt.%) and Sr (363–530 ppm) contents, low Y (4.46–15.9 ppm) and Yb (0.51–1.74 ppm) contents and high Sr/Y ratios of 27–106. The adakitic quartz diorites are further characterized by high MgO (2.63–3.46 wt.%), Mg# (48–54) and ε Hf(t) (6.6–13.4) values, which were probably produced by partial melting of a subducted oceanic slab with a mantle contribution. The adakitic tonalites have very low abundances of compatible elements and relatively low ε Hf(t) values (3.5–10.3), and are interpreted to have formed by partial melting of Neoproterozoic mafic lower crust. Upwelling asthenosphere, triggered by rollback of the subducting Bangong–Nujiang (Meso-Tethys) oceanic plate, provided the necessary heat for slab and lower crust melting, resulting in the geochemical diversity of the coexisting felsic intrusive rocks. Contrary to other models, this study further demonstrates that the Bangong–Nujiang oceanic plate was subducted southward beneath the Lhasa terrane during the Early Jurassic.
Keywords: Adakitic rocks; slab melting; Early Jurassic; Bangong-Nujiang (Meso-Tethys) Ocean; southern Lhasa sub-terrane

Early Neoproterozoic granitic gneisses in the Chinese Eastern Tianshan: Petrogenesis and tectonic implications - Huang, Bo-Tao; He, Zhenyu; Zhang, Zeming; Klemd, Reiner; Zong, Keqing; Zhao, Zhi-Dan (Journal of Asian Earth Sciences, 2015)
Early Neoproterozoic granitic gneisses are known from several locations such as the Xingxingxia, Alatage and Baluntai areas in the Central Tianshan Arc Terrane of the Chinese Eastern Tianshan, which is one of several Precambrian microcontinents within the southern Central Asian Orogenic Belt (CAOB). The petrogenesis and the tectonic significance of the early Neoproterozoic granitic gneisses have not been well constrained yet, resulting in an ambiguous understanding of the early tectonothermal evolution of the Chinese Eastern Tianshan. Geochronological results suggest that the protoliths of these granitic gneisses formed during a relatively short time period between ca. 970 and 915 Ma, mainly clustering at ca. 940 Ma. These peraluminous to strongly peraluminous granitic rocks show a common geochemical S-type granite affinity, involving low CaO, Na2O, Th and Y contents. Zircon saturation thermometry and Ti-in-zircon thermometry yielded a relatively low crystallization temperature of approximately 750–800 °C for the magmatic protolith of the granitic gneisses. Zircon Hf isotopic compositions of the Xingxingxia and Alatage granitic gneisses show εHf(t) values of −5.4 to 4.2, with TDM2 model ages of 1.53–2.14 Ga, indicating that their protoliths were derived by the recycling of older continental crust. We suggest that the early Neoproterozoic granitic rocks in the Chinese Eastern Tianshan were formed along an active continental margin. Furthermore, we propose that the Central Tianshan Arc Terrane was located at the periphery of Rodinia and separated from the Tarim Craton terrane in the early Neoproterozoic.<br
Keywords: CAOB; Central Tianshan Arc Terrane; Neoproterozoic; Rodinia supercontinent; S-type granite affinity

Geochemical evidence for Paleozoic crustal growth and tectonic conversion in the Northern Beishan Orogenic Belt, southern Central Asian Orogenic Belt - Yuan, Yu; Zong, Keqing; He, Zhenyu; Klemd, Reiner; Jiang, Hongying; Zhang, Wen; Liu, Yongsheng; Hu, Zhaochu; Zhang, Zeming (Lithos, 2018)
The Beishan Orogenic Belt is located in the central southernmost part of the Central Asian Orogenic Belt (CAOB), which plays a key role in understanding the formation and evolution of the CAOB. Granitoids are the documents of crustal and tectonic evolution in orogenic belts. However, little is known regarding the petrogenesis and geodynamic setting of the widely distributed Paleozoic granitoids in the Northern Beishan Orogenic Belt (NBOB). The present study reveals significant differences concerning the petrogenesis and tectonic setting of early and late Paleozoic granitoids from the NBOB. The early Paleozoic granitoids from the 446–430 Ma Hongliuxia granite complex of the Mazongshan unit and the 466–428 Ma Shibanjing complex of the Hanshan unit show classic I-type granite affinities as revealed by the relative enrichment of LILEs and LREEs, pronounced depletions of Nb, Ta and Ti and the abundant presence of hornblende. Furthermore, they are characterized by strongly variable zirconεHf(t) values between − 16.7 and + 12.8 and evolved plagioclase Sr isotopic compositions of 0.7145–0.7253, indicating the involvement of both juvenileand ancient continental crust in the magma source. Thus, we propose that the early Paleozoic granitoids in the NBOB were generated in a subduction-related continental arc setting. In contrast, the late Paleozoic 330–281 Ma granitoids from the Shuangjingzi complex of the Hanshan unit exhibit positive zircon εHf(t) values between + 5.8 and + 13.2 and relatively depleted plagioclase Sr isotopic compositions of 0.7037–0.7072, indicating that they were mainly formed by remelting of juvenile crust. Thus, an intra-plate extensional setting is proposed to have occurred during formation of the late Paleozoic granitoids. Therefore, between the early and late Paleozoic, the magma sources of the NBOB granitoids converted from the reworking of both juvenile and ancient crusts during a subduction-induced compressional setting to the remelting of juvenile crust during an intra-plate extensional setting, respectively. The corresponding crustal growth in the southern CAOB is dominated by early Paleozoic lateral accretion of arc complexes and late Paleozoic vertical addition of juvenile material from the mantle.
Keywords: Paleozoic granitoids; Crustal growth; Tectonic conversion; Northern Beishan Orogenic Belt; Central Asian Orogenic Belt (CAOB)

Late Cretaceous tectonothermal evolution of the southern Lhasa terrane, South Tibet: Consequence of a Mesozoic Andean-type orogeny - Dong, Xin; Zhang, Zeming; Klemd, Reiner; He, Zhenyu; Tian, Zuolin (Tectonophysics, 2018)
The Lhasa terrane of the southern Tibetan Plateau participated in a MesozoicAndean-type orogeny caused by the northward subduction of the Neo-Tethyan oceanic lithosphere. However, metamorphic rocks, which can unravel details of the geodynamic evolution, are rare and only exposed in the south-eastern part of the Lhasa terrane. Therefore, we conducted a detailed petrological, geochemical and U–Pb zircon geochronological study of the late Cretaceousmetamorphic rocks and associated gabbros from the Nyemo inlier of the southern Lhasa terrane. The Nyemo metamorphic rocks including gneisses, schists, marbles and calc-silicate rocks, experienced peak amphibolite-faciescontact metamorphism under P–T conditions of 3.5–4.0 kbar and 642–657 °C with a very high geothermal gradient of 45–50 °C/km, revealing a distinct deflection from the steady-state geotherm during low-pressure metamorphism. Inherited magmatic zircon cores from the metamorphic rocks yielded protolithages of 197–194 Ma, while overgrowth zircon rims yielded metamorphic ages of ca. 86 Ma. Whole-rock chemistry and zircon Hf isotopes suggest that the protoliths of the gneisses and schists are andesites and tuffs of the early JurassicSangri Group, which were derived from a depleted mantle source of a continental arc affinity. The coeval intimately-associated gabbro (ca. 86 Ma) crystallized under P–T conditions of 3.5–5.3 kbar and 914–970 °C, supplying the heat flux high enough to cause the contact metamorphism of the Sangri Group rock types. We propose that the intrusion of the gabbro and a simultaneous pressure increase of up to 4.0 kbar, which is related to crustal thickening due to crustal overthrusting and the intrusion of mafic material, resulted in the late Cretaceous metamorphism of the early Jurassic Sangri Group during an Andean-type orogeny. Furthermore the Nyemo metamorphic rocks, which have previously been considered to represent slivers of the Precambrianmetamorphic basement of the Lhasa terrane, are late Cretaceous metamorphic supracrustal rocks.
Keywords: Late Cretaceous contact metamorphism; Gabbroic intrusion; Intrusion-related perturbed geothermal gradient; Andean-type orogeny; Southern Lhasa terrane

Mesoproterozoic continental arc magmatism and crustal growth in the eastern Central Tianshan Arc Terrane of the southern Central Asian Orogenic Belt: Geochronological and geochemical evidence - He, Zhenyu; Klemd, Reiner; Zhang, Zeming; Zong, Keqing; Sun, Li-Xin; Tian, Zuolin; Huang, Bo-Tao (Lithos, 2015)
Numerous microcontinents are known to occur in the Central Asian Orogenic Belt (CAOB), one of the largest accretionary orogens and the most significant area of Paleozoic crustal growth in the world. The evolution of the Precambrian crust in these microcontinents is central to understanding the accretionary and collisional tectonics of the CAOB. Here, we present systematic zircon U–Pb dating and Hf isotope studies of Mesoproterozoic gneissic granitoids from the eastern Central Tianshan Arc Terrane (CTA) of the southern CAOB. The investigated intermediate to felsic (SiO2 = 60.48–78.92 wt.%) granitoids belong to the calcic- to calc-alkaline series and usually have pronounced negative Nb, Ta and Ti anomalies, relative enrichments of light rare earth elements (LREEs) and large ion lithophile elements (LILEs) while heavy rare earth elements (HREEs) and high field strength elements (HFSEs) are depleted, revealing typical active continental margin magmatic arc geochemical characteristics. These spatially-distant rocks show consistent zircon U–Pb crystallization ages from ca. 1.45 to 1.40 Ga and thus constitute a previously unknown Mesoproterozoic continental magmatic arc covering hundreds of kilometers in the eastern segment of the CTA. Furthermore the high and mainly positive zircon εHf(t) values between − 1.0 and + 8.6 and the zircon Hf model ages of 1.95 to 1.55 Ga, which are slightly older than their crystallization ages, suggest that they were mainly derived from rapid reworking of juvenile material with a limited input of an ancient crustal component. Therefore, the formation of these granitoids defines an extensive Mesoproterozoic intermediate to felsic, subduction-related intrusive magmatic arc activity that was active from at least 1.45 to 1.40 Ga, involving significant juvenile continental growth in the eastern segment of the CTA. Furthermore the zircon U–Pb and Hf isotopic data challenge the common belief that the CTA was part of the Tarim Craton during Paleo- to Mesoproterozoic times. However, the southern Beishan microcontinents and the CTA have similar zircon U–Pb and Hf isotopic signatures, indicating a similar Precambrian tectonothermal evolution for both. This finding provides new and important constraints on the Precambrian crustal evolution of the microcontinents in the southern CAOB.<br
Keywords: Zircon U–Pb geochronology and Hf isotopes; Crustal growth; Mesoproterozoic continental magmatic arc; Chinese Eastern Tianshan; Central Asian Orogenic Belt

Mesoproterozoic juvenile crust in microcontinents of the Central Asian Orogenic Belt: evidence from oxygen and hafnium isotopes in zircon - He, Zhenyu; Klemd, Reiner; Yan, Li-Li; Lu, Tianyu; Zhang, Zeming (Scientific Reports, 2018)
We report in situ O and Hf isotope data of zircon grains from coeval Mesoproterozoic (ca. 1.4 Ga) igneous metamafic (amphibolite) and granitic rocks of the Chinese Central Tianshan microcontinent (CTM) in the southern Central Asian Orogenic Belt (CAOB). Zircon grains from amphibolite have mantle-like δ18OVSMOW values of 4.7–5.6‰ and juvenile Hf isotopic compositions (εHf(t) = 8.4–15.3; TDMC = 1.57–1.22 Ga), whereas those from granitic rocks have δ18OVSMOW values of 5.6–7.0‰ and evolved Hf isotopic compositions (εHf(t) = −1.0–8.2; TDMC = 2.09–1.62 Ga). Zircon O–Hf isotopic compositions of the metamafic and granitic rocks provide evidence for Mesoproterozoic (ca. 1.4 Ga) crustal growth and a substantial Palaeoproterozoic supracrustal component in the CTM. These findings and previous studies, reporting ca. 1.4 Ga magmatic rocks from other microcontinents of the CAOB, suggest that a large belt of Mesoproterozoic (ca. 1.4 Ga) juvenile continental crust formed in a continental terrane, fragments of which now occur over a distance of more than a thousand kilometres in the southern CAOB.<br
Keywords: Geochemistry; Petrology; Precambrian geology

Origin and geodynamic significance of the early Mesozoic Weiya LP and HT granulites from the Chinese Eastern Tianshan - Mao, Ling-Juan; He, Zhenyu; Zhang, Zeming; Klemd, Reiner; Xiang, Hua; Tian, Zuolin; Zong, Keqing (Lithos, 2015)
The Chinese Tianshan in the southwestern part of the Central Asian Orogenic Belt (CAOB) is characterized by a variety of high-grade metamorphic rocks, which provide critical constraints for understanding the geodynamic evolution of the CAOB. In this paper, we present detailed petrological and zircon U–Pb geochronological studies of the Weiya low-pressure and high-temperature (LP-HT) granulites of the Chinese Eastern Tianshan. These granulites were previously considered to be a product of a regional metamorphic orogenic event. Due to different bulk-rock chemistries the Weiya granulites, which occur as lenses within the contact metamorphic aureole of the Weiya granitic ring complex, have a variety of felsic–pelitic and mafic granulites with different textural equilibrium mineral assemblages including garnet–cordierite–sillimanite-bearing granulites, cordierite–sillimanite-bearing granulites, cordierite–orthopyroxene-bearing granulites, and orthopyroxene–clinopyroxene-bearing granulites. Average P–T thermobarometric calculations and conventional geothermobarometry indicates that the Weiya granulites underwent early prograde metamorphism under conditions of 600–650 °C at 3.2–4.2 kbar and peak metamorphism of 750–840 °C at 2.9–6.3 kbar, indicating a rather high geothermal gradient of ca. 60 °C/km. Zircon U–Pb LA–ICP–MS dating revealed metamorphic ages between 244 ± 1 to 237 ± 3 Ma, which are in accordance with the crystallization age of the Weiya granitic ring complex. We suggest that the formation of the Weiya granulites was related to contemporaneous granitic magmatism instead of a regional metamorphic orogenic event. In addition, a Late Devonian metamorphic age of ca. 380 Ma was recorded in zircon mantle domains from two pelitic samples which is consistent with the metamorphic age of the Xingxingxia metamorphic complex in the Chinese Eastern Tianshan. This suggests that the mantle domains of the zircon grains of the Weiya granulites probably formed during the Late Devonian regional metamorphism and were overprinted by the Early Triassic contact metamorphism. Therefore, Early Triassic geodynamic models for the southwestern part of the CAOB, which are based on a previously suggested regional metamorphic orogenic event of the Weiya granulites, need to be viewed with caution.<br
Keywords: Central Asian Orogenic Belt; Chinese Eastern Tianshan; Weiya granulites; Early Triassic; Contact metamorphism; Geodynamic setting